Farmer-entrepreneurs, agricultural innovation, and explosive research and development cycles - Jo\~ao Ricardo Faria; Franklin G. Mixon (Administrative Sciences, 2016)
Private sector research and development (R&D) in food processing has seen a growing share of agricultural R&D. This paper analyzes market and technological links between farmer-entrepreneurs and food processing firms. It is shown that processing sector R&D tends to display explosive cycles. To avoid explosive cycles, the processing sector sets the R&D growth path and its target. Dynamic adjustments are related to the shadow price of R&D and farm output price. In equilibrium, the effects of increases in technological innovations (e.g., at the farm level, in public agricultural research, from entrepreneurial talent, in processing sector R&D, and in the price of final goods) on agricultural price and output are positive. The patent race does not affect steady-state agricultural price and output, nor processing sector R&D; it only reduces the opportunity cost of R&D.
Keywords: 350; agricultural innovations; research and development cycles